2000
DOI: 10.1161/01.hyp.35.6.1248
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Reduces Norepinephrine Release Through a Nitric Oxide Mechanism in Rat Hypothalamus

Abstract: Abstract-Angiotensin (Ang)-(1-7) elicits a facilitatory presynaptic effect on peripheral noradrenergic neurotransmission, and because biological responses to the heptapeptide on occasion are tissue specific, the present investigation was undertaken to study its action on noradrenergic neurotransmission at the central level. In rat hypothalamus labeled with [ 3 H]-norepinephrine, 100 to 600 nmol/L Ang-(1-7) diminished norepinephrine released by 25 mmol/L KCl. This effect was blocked by the selective angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
1
30
1
Order By: Relevance
“…10,41 Previous studies have demonstrated that Ang-(1-7) inhibits NE release via a NO-dependent mechanism in the rat hypothalamus. 42,43 In the current study, markedly increased glutamate and NE levels and a reduced level of GABA in the PVN were observed in HS rats compared to that in NS rats. Moreover, we found that HS rats had a higher level of tyrosine hydroxylase (TH; a marker used to recognize adrenergic neurons) and a lower level of 67 kDa isoform of glutamate decarboxylase (GAD67; a marker used to identify GABAergic neurons) expression within the PVN compared to that in NS rats, implying improved excitatory adrenergic activities and attenuated GABAergic activity in the PVN.…”
Section: -37supporting
confidence: 52%
“…10,41 Previous studies have demonstrated that Ang-(1-7) inhibits NE release via a NO-dependent mechanism in the rat hypothalamus. 42,43 In the current study, markedly increased glutamate and NE levels and a reduced level of GABA in the PVN were observed in HS rats compared to that in NS rats. Moreover, we found that HS rats had a higher level of tyrosine hydroxylase (TH; a marker used to recognize adrenergic neurons) and a lower level of 67 kDa isoform of glutamate decarboxylase (GAD67; a marker used to identify GABAergic neurons) expression within the PVN compared to that in NS rats, implying improved excitatory adrenergic activities and attenuated GABAergic activity in the PVN.…”
Section: -37supporting
confidence: 52%
“…In contrast, ANG-(1-7) is also known to mediate sympathoexcitatory effects in RVLM (12) and paraventricular nucleus of the hypothalamus (39). However, recent data have shown that ANG-(1-7) inhibits norepinephrine release in hypothalamus through nitric oxide pathway in different models of hypertension and prevents the ANG II stimulatory effect in this region (13)(14)(15). Even though some acute studies have shown an excitatory effect of ANG-(1-7), it is important to consider that chronic studies clearly show that ANG-(1-7) mediates antihypertensive effects in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Probably not. Many previous studies suggest that, in addition to the interaction with the A-779-sensitive receptor Mas, [7][8][9][10]14 Ang (1-7) is capable of interacting with ACE 4 and AT 1 3,30 and AT 2 -like receptors 31 or, more likely, with Mas-AT 1 and/or Mas-AT 2 oligomers. 14,32 Several studies have shown that Ang(1-7) may play an important hemodynamic role by increasing baroreflex sensitivity, 33 modulating vascular reactivity to angiotensin II 27,28 and bradykinin, 4,19,20,23 and influencing cardiac output.…”
Section: Perspectivesmentioning
confidence: 99%